2020
DOI: 10.1073/pnas.1918986117
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5 regulates anti–PD-1 therapy response by modulating lactate and suppressive immune cell accumulation in tumor microenvironment

Abstract: Although immune checkpoint blockade (ICB) therapy has revolutionized cancer treatment, many patients do not respond or develop resistance to ICB. N6-methylation of adenosine (m6A) in RNA regulates many pathophysiological processes. Here, we show that deletion of the m6A demethylase Alkbh5 sensitized tumors to cancer immunotherapy. Alkbh5 has effects on m6A density and splicing events in tumors during ICB. Alkbh5 modulates Mct4/Slc16a3 expression and lactate content of the tumor microenvironment and the composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
367
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 404 publications
(375 citation statements)
references
References 53 publications
8
367
0
Order By: Relevance
“…R-2-hydroxyglutarate (R-2HG), an oncometabolite resulting from the conversion of α-ketoglutarate by mutant IDH1/2 enzymes, has also been shown to specifically inhibit FTO and proliferation of leukemic or GBM cells [ 13 ]. More recently, a study also reported the efficacy of a specific ALKBH5 inhibitor, ALK04, in reducing tumor growth of melanoma cells [ 57 ]. Several other compounds, including (rhein, MO-I-500, Entacapone, NCDPCB, CHTB), have also been described as FTO or ALKBH5 potential inhibitors, although their anti-tumoral action has not been demonstrated [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…R-2-hydroxyglutarate (R-2HG), an oncometabolite resulting from the conversion of α-ketoglutarate by mutant IDH1/2 enzymes, has also been shown to specifically inhibit FTO and proliferation of leukemic or GBM cells [ 13 ]. More recently, a study also reported the efficacy of a specific ALKBH5 inhibitor, ALK04, in reducing tumor growth of melanoma cells [ 57 ]. Several other compounds, including (rhein, MO-I-500, Entacapone, NCDPCB, CHTB), have also been described as FTO or ALKBH5 potential inhibitors, although their anti-tumoral action has not been demonstrated [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, KD of FTO sensitized melanoma cells to IFNγ, thereby reducing resistance to anti-PD-1 therapy. Similarly, RNA demethylase ALKBH5 KO showed significant reduction in tumor growth and prolonged mouse survival during ICPi therapy in B16 melanoma and CT26 colon cancer mouse models [ 183 ]. This was due to ALKBH5 altering gene expression and splicing that leads to changes in lactate levels in the TME.…”
Section: Targeting Methylation In the Treatment Of Human Diseasementioning
confidence: 99%
“…Strikingly, many different classes of antitumor drugs have been found being associated with glycolysis-induced resistance: a large number of different chemotherapeutics [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , large molecule therapeutics like monoclonal antibodies (mAb) targeting a variety of different antigens, including immune checkpoint inhibitors [1 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , hormone antagonists [1 , 32] , targeted, small molecule therapeutics like tyrosine kinase inhibitors (TKI) [1 , [33] , [34] , [35] , [36] , glucocorticoids [1 , 37] , and ionizing radiation [1 , 38] . While the mechanisms underlying glycolysis-induced drug resistance will be discussed in a later section, it can be anticipated that the broad range of therapeutic agents associated with glycolysis-induced resistance, spanning from small molecule drugs to large-sized molecules like mAbs, likely involves different mechanisms that may vary according to the different classes of molecules.…”
Section: Classes Of Antitumor Drugs That Are Associated With Glycolysmentioning
confidence: 99%